Pengembangan Produk Kerajinan Batik Kayu Desa Krebet Pasca Pandemi Covid-19 - Nur, Christmastuti (Universitas Nusantara PGRI Kediri, 2023)
Wooden batik handicraft products from Krebet Village are included in the category of products that are in demand by the international market because of their uniqueness and quality. When the Covid-19 pandemic hit, export activities immediately faltered because almost all foreign consumers stopped ordering Indonesian handicraft products. Through this incident, the craftsmen in Krebet Village realized that it was impossible to continue to depend on one market niche for the continuity of their business. This Community Service activity aims to develop designs for export-oriented wooden batik products after the Covid-19 Pandemic. The implementation of this community service uses the science and technology diffusion method in the form of activities in the form of counseling regarding insights into export market trends as well as assistance in making sample products based on new export market targets. The output of this activity is in the form of serving trays and candle holders with a design style that fits European market target.